EXPLAIN IN STEPS PLEASEE y = 2x + 1 y = 6 -3x

Question

EXPLAIN IN STEPS PLEASEE
y = 2x + 1
y = 6 -3x

in progress 0
Ngọc Khuê 2 weeks 2021-09-02T19:55:46+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-02T19:57:12+00:00

    Answer:

    x = 1; y = 3

    Step-by-step explanation:

    Get the unknowns on one side of the equal sign and the known numbers on the other:

    EQUATION 1: y = 2x + 1 (subtract 2x from both sides)

    y -2x = 1

    EQUATION 2: y = 6 -3x (add 3x to both sides)

    y + 3x = 6

    Now we have two simultaneous equations:

    y -2x = 1

    y + 3x = 6

    subtraction gives -5x = -5 so x = 1

    Substitute x = 1 into one of the original equations to find y.

    y + 3x = 6 becomes y + 3 = 6, so y = 3

    0
    2021-09-02T19:57:38+00:00

    7Y=-1X

    Step-by-step explanation:

    Ya me la pusieron a mi y soy muy bueno en matemáticas

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )